Study of the Toxic effect of new Cadmium ( II) complex [ CdL2]. 1/2H2O on GPT and ALP activity in some organs of female mice comparable with anitumor drug Cyclophosphamide (CP) (Baghdad Science Journal, 2015)
Cadmium has been known to be harmful to human healthy , manily Via contaminated drinking water , food supplies , tobacco and industrial pollutant . The aim of this study was to determine the toxicity of new Cadmium (II) complex ( Bis[ 5- ( P- nitrophenyl ) – ? 4 – Phenyl- 1,2,4- triazole -3- dithiocarbamatohydrazide] cadmium (II) Hydra ( 0.5) and compare it with anticancer drug cyclophosphamide ( CP) in female albino mice . This complex causes to several alterations in Enzymatic activity of Glutamate Pyruvate Transaminase (GPT) and Alkaline Phosphatase (ALP ) in three organs after the treatment of mice with different doses of a new cadmium (II) complex ( 0.09 / 0.25ml , 0.18/ 0.5ml and 0.25mg /0.7 ml /30 gm of mouse ) for three days by the decreased of Glutamate Pyruvate Transaminase activity in lung , Liver and kidney , while the Alkaline Phosphatase activity was increased in kidney , lung and liver . The results were indicated that no significant differences ( P > 0.05 ) in Glutamate Pyruvate Transaminase activity between the treatment of mice with cadmium ( II ) complex and cyclophosphamide (CP) in the liver , kidney and Alkaline Phosphatase activity in the liver at each three doses .